Peningkatan Motivasi Pembelajaran IPS Melalui Strategi Role Playing - Alifa Nur Latifah; Sri Wulandari; Prihantini Prihantini (Universitas Palan, 2024)
This research has the aim of knowing how the effect of role playing learning on increasing social studies learning motivation in 6th grade students of SD Bojong Salam 4. This study uses an experimental method. or experiment. Based on quantitative data analysis, it can be concluded that this role playing learning model has a significant effect on increasing students' learning motivation.